1998
DOI: 10.1016/s0002-9440(10)65692-1
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Enhancement of Skin Neoplasia by Chronic Stimulation of Growth Factors

Abstract: Although numerous epidemiological studies have shown that inorganic arsenicals cause skin cancers and hyperkeratoses in humans , there are currently no established mechanisms for their action or animal models. Previous studies in our laboratory using primary human keratinocyte cultures demonstrated that micromolar concentrations of inorganic arsenite increased cell proliferation via the production of keratinocyte-derived growth factors. As recent reports demonstrate that overexpression of keratinocyte-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
118
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(128 citation statements)
references
References 51 publications
(60 reference statements)
9
118
1
Order By: Relevance
“…The decrease of Nrf2 activation in response to high levels of oxidative stressors observed in As-TM cells, coupled with their acquired apoptotic resistance might increase the likelihood to acquire heritable oxidative DNA damage [7,9]. This may help explain the remarkable co-carcinogenic effects of arsenic and UV irradiation observed in mouse models of dermal carcinogenesis but the absence of activity for arsenic alone [3,4]. Our previous study indicated that exogenous GSH might markedly suppress hypochlorous acid-induced Nrf2 activation in mouse macrophages [50], suggesting the enhanced GSH levels in As-TM cells might be a critical factor for the weakened Nrf2 activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease of Nrf2 activation in response to high levels of oxidative stressors observed in As-TM cells, coupled with their acquired apoptotic resistance might increase the likelihood to acquire heritable oxidative DNA damage [7,9]. This may help explain the remarkable co-carcinogenic effects of arsenic and UV irradiation observed in mouse models of dermal carcinogenesis but the absence of activity for arsenic alone [3,4]. Our previous study indicated that exogenous GSH might markedly suppress hypochlorous acid-induced Nrf2 activation in mouse macrophages [50], suggesting the enhanced GSH levels in As-TM cells might be a critical factor for the weakened Nrf2 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Arsenic is also carcinogenic in rodent models, producing liver, lung, ovary and adrenal tumors after transplacental exposure [2] and skin tumors in combination with ultraviolet (UV) irradiation or phorbol esters in mice [3,4]. However, arsenic alone does not appear to induce skin cancer in these mouse models [2][3][4], suggesting events associated with arsenic-induced dermal carcinogenesis may be distinct from other target tissues. Accumulating evidence suggests that oxidative stress occurs in response to arsenic exposure [5,6] and may be one factor in dermal arsenic carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of these effects of arsenic on the development of diseases are not known. But previous studies indicated that alteration of cell proliferation contributes to its carcinogenicity [5]. On the other hand, arsenic has been used to treat cancers and it brings complete remission of acute promyeloid leukemia [6] .…”
Section: Introductionmentioning
confidence: 99%
“…In transgenic Tg.AC mice, As acts as co-promoter during skin carcinogenesis in standard two-stage models (20). These studies have suggested that transforming growth factor-α (TGFα) and granulocyte/macrophage-colony stimulating factor may be useful biomarkers for As-associated carcinogenesis in keratinocytes; data from As-exposed human subjects support this hypothesis (20). It is likely, however, that the picture is much more complex than this and that the genes involved are more numerous.…”
mentioning
confidence: 99%